2016
DOI: 10.21608/mnj.2016.149324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Applying Spontaneous Pushing Technique During Second Stage of Labor on Women''''s Early Postpartum Fatigue

Abstract: The aim of this study was to evaluate the effect of applying of spontaneous pushing technique during second Stage of labor in early postpartum fatigue. Methods: A quasiexperimental research design was used to carry out this study at the Labor and delivery unit of Mansoura University Hospital on 100 primigravida women at ≤37 gestational weeks, who were selected by purposive sampling technique. They were free from any medical and obstetric problems, can read and write. They were assigned either to the control or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Time duration of the second stage of labor: Two studies reported that spontaneous pushing gave a shorter time duration in the second stage of labor compared to Valsalva pushing. 21,23 In contrast, a third study reported that Valsalva pushing produced a shorter duration. 22 The combined effect sizes of the three studies [21][22][23] showed a high level of heterogeneity (I 2 = 98%).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…Time duration of the second stage of labor: Two studies reported that spontaneous pushing gave a shorter time duration in the second stage of labor compared to Valsalva pushing. 21,23 In contrast, a third study reported that Valsalva pushing produced a shorter duration. 22 The combined effect sizes of the three studies [21][22][23] showed a high level of heterogeneity (I 2 = 98%).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 98%
“…21,23 In contrast, a third study reported that Valsalva pushing produced a shorter duration. 22 The combined effect sizes of the three studies [21][22][23] showed a high level of heterogeneity (I 2 = 98%). The summary effect size from the random effects model was not statistically significant, thus not supporting the benefit of spontaneous pushing in reducing the duration of labor [overall effect size = -0.89 (95% CI = -3.39, 1.28, p = .376)].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“… Parturient women during second stage of labor and fulfilled the criteria of vaginal delivery without contraindications. It was designed by researcher after reviewing related literatures regarding the study(Elzihiri et al, 2016), it included the following two parts: First part Socio-demographic data, it included (age, education level, occupation and residence).  Second part concerning with current pregnancy and labor data as (gestational age, antenatal care received, onset of antenatal care, number of antenatal care visits, duration of labor pain until the time of admission, frequency of uterine contraction, bladder condition and enema performed).Tool II: Physical assessment and observation sheet during labor:-This tool was adopted from (Mohamed, 2013) and was used to assess maternal and newborn conditions, which included general examination on admission (maternal vital signs, anthropometric measurements, vaginal examination, condition of membrane, amniotic fluid color and uterine contractions) and general examination during second stage of labor (vital signs , fetal heart rate (FHR), oxytocin use of augmentation, increase in oxytocin dose during the second stage of labor, station of fetal head at initiation of pushing, uterine contractions, duration of uterine contraction, number and duration of pushing during each contraction) Tool III: Visual Analogue Scale (VAS): It was used to assess the level of pain.…”
mentioning
confidence: 99%